A Global Perspective on Psycho-Educational Assessment. Issue 1 (15th July 2015) - Gilmore, Linda; Islam, Shaheen; Su, Hui; Younesian, Sharifeh
Abstract : For psychologists in less developed countries, psycho-educational assessment is often challenging due to a lack of specialist training and a scarcity of appropriate, psychometrically robust instruments. This article focuses on school psychology and psycho-educational assessment in three countries: Bangladesh, China and Iran. Despite differences in demographic and cultural features, these countries share similar issues that restrict the practice of psycho-educational assessment. We conclude that it is important for psychologists in Western countries to support professional training and testing practices in less developed countries.